Formulasi Sampo Antiketombe Liofilisat Buah Mengkudu (Morinda citrifolia): Aktivitas Antijamur, Uji Stabilitas Dan Keamanan Melalui HET-CAM - Nur Khairi; Budiman Yasir; Maulita Indrisari (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Dandruff is a common issue caused by the overgrowth of Malassezia furfur on the scalp. This study aims to develop a safe antidandruff shampoo formulation based on lyophilized noni fruit (Morinda citrifolia L.) and evaluate its effectiveness in combating dandruff. The lyophilized noni fruit was tested for its antifungal activity at five concentrations: 2%, 4%, 6%, 8%, and 10%, and then formulated into shampoo in three concentrations: F1 (6%), F2 (8%), and F3 (10%). The effectiveness of the shampoo formulations was tested against Malassezia furfur using the agar diffusion method. The safety of the formulations was also evaluated using the HET-CAM method to ensure their non-irritating properties. The results indicated that lyophilized noni fruit exhibited significant antifungal activity, with the largest inhibition zone observed at 10% concentration (23.16 ± 5.36 mm), which was not significantly different from the positive control (ketoconazole). Additionally, the HET-CAM test showed no irritation for all formulations, with an irritation score of 0. This study concludes that lyophilized noni fruit shampoo can serve as an effective and safe natural alternative for dandruff treatment.